Problem-Based Learning Activities Management to Enhance Strong Citizenship Skills Among Secondary School Year 3 Students in Chainat Municipality-Supported Schools - Payukkririntorn, Nisachol; Panyavuttrakul, Wasin (Journal of Buddhist Education and Research (JBER), 2025)
The research has the following objectives: 1) to study the current conditions of problem-based learning activities to promote strong citizenship among 3rd-grade students at Chai Nat Municipality School; and 2) to develop problem-based learning activities aimed at enhancing the strong citizenship competencies of the same group of students. This research is qualitative, with a group of informants consisting of 1) 3 Social Studies teachers, 2) 2 homeroom teachers, 3) 5 parental representatives, and 4) 40 third-grade students. The research was conducted through document studies, interviews, observations, document analysis, inductive summary analysis, triangulation of data quality, and descriptive analytical reporting. The study's results indicated that: 1) current conditions of learning activities: 1.1) In terms of teachers, the role of teachers in promoting strong citizenship for students is present, but there is a lack of up-to-date resources on social issues related to promoting strong citizenship. 1.2) In terms of students, students have a basic understanding of good citizenship and its role, and they show respect for the law and school rules. However, they do not fully recognize the importance of being strong citizens, lack motivation to learn, and face issues with participation in activities. 1.3) In terms of content, there is a connection between the content of citizenship, culture, and societal living. However, the content relies more on memorization than practical application, with no analytical breakdown. 1.4) In terms of learning media, there is training in exercising citizenship rights in real situations, using video clips and infographics to engage students. However, there is a lack of budget for developing modern media. 1.5) In terms of learning activities, no formal learning activities to promote strong citizenship have been organized, but the school plans to implement such activities in the future. 1.6) In terms of environment and atmosphere, the school has created a suitable physical environment conducive to learning. 2. The development of learning activities showed that students were able to demonstrate strong citizenship as follows: 2.1) Citizenship respecting rights: Students are willing to express differing opinions, understand their basic rights as students, and respect the classroom rules. 2.2) Citizenship being responsible for roles and duties: Students adhere to classroom rules, maintain cleanliness, are punctual, submit homework on time, and clean their designated areas. 2.3) Citizenship participating critically: Students stay updated with news via reliable online sources and television, and engage in community service outside of school. 2.4) Citizenship as agents of change: Students conducted peer teaching activities during lunch breaks to improve Thai reading skills, voiced their opinions about school development in a suggestion box, and led a waste separation campaign by collecting bottles for recycling to fund school activities.